Kontribusi Seft-Efficacy Dan Mathematics Anxiety Terhadap Kemampuan Penalaran Matematika Siswa - Maesya Firdaus, Denny; Purwanto, Sigid Edy; Nuriadin, Ishaq (International Journal of Progressive Mathematics Education, 2021)
Background. Self-efficacy and mathematics anxiety are like two linked currencies, when a student's level of self-efficacy is high, mathematics anxiety is low and vice versa, this condition is related when learning mathematics. Purpose This study aims to determine the relationship between self-efficacy and mathematics anxiety on students' mathematical reasoning abilities. This research method uses a survey method, the population is all elementary school students in class VI in Ciwandan District which consists of 4 clusters and a sample of 100 students is taken with a sampling technique using multistage random sampling and for research instruments in the form of questionnaires and tests. The research results show that the results of the first hypothesis show that there is a relationship between self-efficacy and students' mathematical reasoning abilities with a moderate degree of correlation and a positive relationship. The second hypothesis is that there is a relationship between mathematics anxiety and students' mathematical reasoning abilities, which has a moderate degree of correlation and a negative relationship. The third hypothesis is that there is a relationship between self-efficacy and mathematics anxiety on students' mathematical reasoning abilities with a strong relationship in a positive direction, while the coefficient of determination is 0.386, meaning that the contribution of mathematical reasoning abilities is 38.6%, which can be predicted based on self-efficacy and mathematics. anxiety, while the remaining 61.4% can be predicted from other factors.   Latar Belakang. Self-efficacy dan mathematics anxiety bagaikan dua mata uang yang saling berikatan, ketika tingkat self-efficacy siswa tinggi maka mathematics anxiety rendah begitupula sebaliknya, kodisi ini berhubungan ketika mempelajari matematika. Tujuan Penelitian ini bertujuan untuk mengetahui hubungan self-efficacy dan mathematics anxiety terhadap kemampuan penalaran matematis siswa. Metode Penelitian ini menggunakan metode survei, populasinya, yaitu seluruh siswa Sekolah Dasar kelas VI di Kecamatan Ciwandan yang terdiri dari 4 gugus dan sampel yang diambil sebanyak 100 siswa dengan teknik sampling menggunakan multistage random sampling dan untuk istrumen penelitian berupa kuesioner dan tes. Hasil Penelitian menunjukkan hasil hipotesis pertama diperoleh bahwa terdapat hubungan antara self-efficacy terhadap kemampuan penalaran matematis siswa dengan derajat hubungan korelasi sedang dan bentuk hubungan yang positif. Hipotesis kedua diperoleh bahwa terdapat terdapat hubungan antara mathematics anxiety terhadap kemampuan penalaran matematis siswa mempunyai derajat hubungan korelasi sedang dan bentuk hubungan yang negatif. Hipotesis ketiga diperoleh bahwa terdapat hubungan antara self-efficacy dan mathematics anxiety terhadap kemampuan penalaran matematis siswa dengan derajat hubungan kuat dengan arah positif, sedangkan nilai koefisien determinasi diperoleh sebesar 0,386 artinya kontribusi kemampuan penalaran matematis 38,6% dapat diprediksi berdasarkan self-efficacy dan mathematics anxiety, sedangkan sisanya yaitu 61,4 % dapat diprediksi dari faktor yang lain.